The effect of the fishbowl strategy by using the electronic classroom (Google classroom) on the scientific achievement of fifth-grade students in biology - et.al, Rawaa Mohsen Abdel Karim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify (the effect of the fishbowl strategy using the electronic classroom (Google classroom) on the achievement of fifth-grade students in the science of biology), and to achieve the goal of the research, the researcher adopted the experimental design with partial control for two equal groups, and the research sample was chosen randomly from scientific fifth-grade students from (Imam Al-Sadiq Junior High School for Boys) affiliated to the General Directorate of Education in Baghdad , Rusafa Al-Awla, as it reached (61) students by (30) students in the experimental group, and (31) students in the control group, the two groups of research were rewarded in the variables (chronological age, intelligence, past information test, previous achievement), and the scientific material was specified in the first four chapters of the biology book to be taught, and the behavioral objectives of the chapters were formulated and reached (315) a behavioral purpose representing the six levels of Bloom's classification of the cognitive domain, and the teaching plans were prepared for the two research groups, and the research tool was prepared, which is the achievement test, as it consisted of (50) objective paragraphs, the validity and reliability of the tool was confirmed, as the data were analyzed and processed statistically, using (t-test for two independent samples, alpha Cronbach's coefficient, Kioder Richshadson's equation 20, paragraph difficulty coefficient, discrimination coefficient, and the effectiveness of false alternatives) In light of this the researcher made a number of recommendations And proposals.